Broad snouted caiman (Caiman latirostris) growth under different rearing densities - Poletta, Gisela Laura (2008)
The effect of density on growth in body mass (BM) and total length (TL) of Caiman latirostris hatchlings raised in small pens (area 0.36 m2), for 3 months, was investigated. Twelve animals from each of three clutches were randomly distributed (1, 2 or 3 individuals) to two replicates at low rearing density (LRD: 0.12 m2/individual), medium rearing density (MRD: 0.06 m2/individual) and high rearing density (HRD: 0.04 m2/individual. Growth at LRD [BM: 150.75 ± 43.83 g (SE); TL: 11.58 ± 0.93 cm] and MRD (BM: 141.96 ± 22.55 g; TL: 8.38 ± 1.26 cm) was significantly more than at HRD (BM: 57.19 ± 14.38 g; TL: 4.61 ± 0.89 cm; p < 0.001). Density is important to achieving optimal growth and maintaining the well-being of C. latirostris in commercial ranching programs.